2017
DOI: 10.1111/pace.13038
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroless Catheter Ablation of Cardiac Arrhythmias: A 5‐Year Experience

Abstract: (PACE 2017; 40:425-433) ablation, arrhythmia, fluoroless

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
102
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 33 publications
4
102
0
2
Order By: Relevance
“…Most other studies on fluoroless AF ablation are either small scale or were performed at a low volume (Table ). The only study that included more than 100 fluoroless AF ablations was performed over 5 years by multiple operators at a volume of ≤ 40 per year and required an average procedure time of 194 minutes versus 106 minutes in this study (Table ) . It may not be practical to implement these ablation approaches in a busy, high‐volume EP lab.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most other studies on fluoroless AF ablation are either small scale or were performed at a low volume (Table ). The only study that included more than 100 fluoroless AF ablations was performed over 5 years by multiple operators at a volume of ≤ 40 per year and required an average procedure time of 194 minutes versus 106 minutes in this study (Table ) . It may not be practical to implement these ablation approaches in a busy, high‐volume EP lab.…”
Section: Discussionmentioning
confidence: 99%
“…Another important but often overlooked and understudied aspect of any ablation method involves the cost effectiveness. More recently, several studies have been reported, aiming to minimize or eliminate radiation exposure . However, none of these studies addressed the issue of cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the two largest studies, the current study by Liu and Palmer and another from Razminia et al, (n = 186) complication rates were 1–1.6%. The study by Razminia et al also included 36 patients with cryothermal balloon ablation …”
mentioning
confidence: 99%